Figura žreca u Dežmanovu "Ljutovidu" - Brunčić, Dubravka (Wydawnictwo Naukowe UAM, 2013)
This article analyses a construction of figure of žrec in the introductory canto of historical epic Ljutovid written by Croatian romantic writer Ivan Dežman. Žrec is a religious-magical figure which comprises functions of priest, prophet and magician. By applying reviewed readings of Austin’s speech acts theory, the article focuses on the performative dimension of žrec’s prophetic utterances, different types of prophetic speech and their effects of national integration.
Figure of Žrec in Dežman’s "Ljutovid"
Keywords: discourse; magic; Croatian epics; Ivan Dežman; performative